Outcomes of Parenchyma-Preserving Hepatectomy and Right Hepatectomy for Solitary Small Colorectal Liver Metastasis: A LiverMetSurvey Study - Hosokawa, I (2019)
BACKGROUND: Occasionally, right hepatectomy, rather than parenchyma-preserving hepatectomy, has been performed for solitary small colorectal liver metastasis. The relative oncologic benefits of parenchyma-preserving hepatectomy and right hepatectomy are unclear. This study compared the outcomes of patients with solitary small colorectal liver metastasis in the right liver who underwent parenchyma-preserving hepatectomy and those who underwent right hepatectomy. METHODS: The study population consisted of a multicentric cohort of 21,072 patients operated for colorectal liver metastasis between 2000 and 2015 whose data were collected in the LiverMetSurvey registry. Patients with a pathologically confirmed solitary tumor of less than 30 mm in size in the right liver were included. The short- and long-term outcomes of patients who underwent parenchyma-preserving hepatectomy were compared to those of patients who underwent right hepatectomy. RESULTS: Of the 1,720 patients who were eligible for the study, 1,478 (86%) underwent parenchyma-preserving hepatectomy and 242 (14%) underwent right hepatectomy. The parenchyma-preserving hepatectomy group was associated with lower rates of major complications (3% vs 10%; P < .001) and 90-day mortality (1% vs 3%; P = .008). Liver recurrence occurred similarly in both groups (20% vs 22%; P = .39). The 5-year recurrence-free survival and overall survival rates were similar in both groups. However, in patients with liver-only recurrence, repeat hepatectomy was more frequently performed in the parenchyma-preserving hepatectomy group than in the right hepatectomy group (67% vs 31%; P < .001), and the overall 5-year survival rate was significantly higher in the parenchyma-preserving hepatectomy group than in the right hepatectomy group (55% vs 23%; P < .001). CONCLUSION: Parenchyma-preserving hepatectomy should be considered the standard procedure for solitary small colorectal liver metastasis in the right liver when technically feasible.